PENGARUH PENGGUNAAN AMILUM BIJI DURIAN (Durio Zibethinus L.) SEBAGAI BAHAN PENGHANCUR YANG DITAMBAHKAN SECARA INTERNAL-EKSTERNAL TERHADAP SIFAT FISIK DAN KIMIA TABLET IBUPROFEN - Sugiyono Sugiyono; Hilda Shofia Afriliana; Yulias Ninik Windriati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2013)
ABSTRACT Keyword : durian seeds amylum, disintegrant, ibuprofen tablets. Amylum is a polysaccharide inside plant that was saved as a food reserves in fruit seed. One of the amylum contents is amylose, essentially insoluble in cold water but can absorb large amount of water and expand, so it can be used as a disintegrant of tablets. The aim of this research is to find out the influence of the used of durian seeds amylum as a disintegrant that be added internally-externally toward the physical and chemical properties of ibuprofen tablets.Ibuprofen tablets were prepared by wet granulation method, with levels of amylum as a disintegrant were 10% which added the intragranular-extragranular with a ratio of FI (100%:0%), FII (75%:25%), FIII (50%:50%), FIV (25%:75%), FV (0%:100%). Dried granules obtained were then tested its physical properties include flow rate, angle of repose, and compressibility. Tablets were tested in terms of physical and chemical tablets properties include weight uniformity, hardness, friability, disintegration time and active substance content of tablets. Data obtained were analyzed with a theoretical approach that is done by comparing the statistical literature and that is one way ANAVA analysis with 95% confidence level, followed by a Tuckey test.The result obtained shows that all formulation complied with the requirement of good physical and chemical properties of tablet. The added of durian seeds amylum as a tablets disintegrant with internally-externally method causes difference the physical properties of disintegration time ibuprofen tablets in significant, while at hardness and friability there is no difference in significant.